Gain in 1q is a Common Abnormality in Phyllodes Tumours of the Breast - Kowan J. Jee; Gyungyub Gong; Sei Hyun Ahn; Jeong Mi Park; Sakari Knuutila (Analytical Cellular Pathology)
We studied DNA copy number changes by CGH and allelic imbalance (AI) on 3p by LOH analysis on 22 phyllodes tumours (PT) of the breast in order to gain insight into the genetic basis of tumour progression in PT. Copy number changes were observed in 14 cases (63%). Gain in 1q with 1q21–23 as the minimal overlapping area was seen in 12 cases (55%). The gain was observed both in benign and malignant tumours. Our study did not reveal any DNA copy number changes or allelic loss on 3p. The results suggest that DNA copy number changes are not associated with the histological grade or clinical behaviour of PT and the chromosomal changes on 3p appear to be rare. Colour figure can be viewed on http://www.esacp.org/acp/2003/25‐2/jee.htm.